Penggunaan Text Modeling Untuk Identifikasi Kesalahan Penulisan Kata Pada Teks Pidato Bupati Banggai Sulawesi Tengah - Suparno, Daffa Setiawan; Rosyda, Miftahurrahma (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Typing errors or typography are errors made when typing a document or text, typing errors can occur due to mechanical failure or slipping of the hand or finger. Generally, typing errors are something that often occurs when someone is typing and is considered normal, but this typing error in some contexts can change the meaning of the word or even the meaning of the sentence itself, This causes the need for correction again after someone has finished typing, but the correction process is mostly still manually so the results of the correction depend on how carefully someone makes corrections and how many documents will be corrected. Therefore we need a system that can make corrections quickly and accurately, the correction process can be done by various methods, one of which is using the text modeling method. In this study, the test data used 10 documents of the Banggai Regent's important speech, Central Sulawesi. The text modeling method can be combined with other supporting methods such as word2vec, where word2vec will be used as a recommendation for corrected words. This study creates a system that can correct word errors in important speech documents of the Banggai Regent, Central Sulawesi by using text modeling and Word2Vec methods, the results obtained from the system that has been made are the system has good performance and gets maximum test results